In Vitro Shoot Regeneration of Oil Seed Crop Sesamum indicum L. from Seedling Cotyledon Explant to Lay Ground for Genetic Transformation in Ethiopia - Micheale Yifter Weldemichael; Yemane Tsehaye Bayratsion; Desta Berhe Sbhatu; Girmay Gebresamuel Abraha; Hagos Mohammedseid Juhar; Abraha Birhan Kassa; Fiseha Baraki Sibhatu; Birhanu Debesay Berhe; Tagel Elias Sahle; Mohammed Mebrahtu Mossa; Haftay Abadi Gebru (International Journal of Agronomy)
This study was conducted to develop an efficient regeneration protocol used for sesame genetic transformation. Published regeneration methods using 6-benzylaminopurine (BAP), indol-3-butyric acid (IBA), and α-naphthaleneacetic acid (NAA) were used in this experiment. Cotyledon explants of 14 Ethiopian genotypes collected from Humera Agricultural Research Center (HuARC) were used. Optimized culture conditions were used to investigate the regeneration response of different genotypes. Significant interactions between hormone treatments, MS media, and genotypes for shoot and root regeneration were recorded. Results showed that culture of cotyledons were developed and used as a source of explants for shoot regeneration. The highest shoot number, leaf number, and shoot length were recorded on explants cultured on 1.00 mg·L−1 BAP + 1.00 mg·L−1 NAA in Hirhir and Aberghele, 0.75 mg·L−1 BAP + 1.00 mg·L−1 NAA in Baha Zeyit, and 1.0 mg·L−1 BAP + 1.00 mg·L−1 NAA in Humera 1, respectively. The lowest shoot number, leaf number, and shoot length were observed on explants cultured on the control in Gondar 1, Borkana, and Baha Necho, Borkana and Beha Necho, and Baha Necho, respectively. Genotypes with well-developed shoots were transferred to root induction media. Under rooting media, the best mean, root number, and root length were observed in Aberghele and ACC44 at 0.1 mg·L−1 IBA and 0.2 mg·L−1 NAA, respectively. Standardizing genotypes trait data to mean 0 and unity variance has helped to group 14 genotypes into four distinct clusters. Hirhir, Abeghele, Baha Zeyit, and Humera 1 were the best genotypes. These findings lay ground to Ethiopian sesame to do further genetic transformation aiming at improving the crop.